2010
DOI: 10.1093/jac/dkq216
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre study to evaluate the impact of timing of caspofungin administration on outcomes of invasive candidiasis in non-immunocompromised adult patients

Abstract: Non-albicans Candida species accounted for the majority of IC in caspofungin-treated patients. Improved outcomes were observed for patients initiated with caspofungin within 72 h of positive culture compared with those who received delayed therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 20 publications
0
35
0
2
Order By: Relevance
“…Whereas a shift to non-albicans species of Candida, particularly C. glabrata, has been a cause for alarm among clinicians caring for profoundly ill patients in the hospital (23,26,61), others have suggested that this is not a concern in the current "echinocandin era" (16,56,57). Prior to the availability of the echinocandins, concern over the reduced azole susceptibility of C. glabrata was a major issue for clinicians (10,22,29,32,54).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas a shift to non-albicans species of Candida, particularly C. glabrata, has been a cause for alarm among clinicians caring for profoundly ill patients in the hospital (23,26,61), others have suggested that this is not a concern in the current "echinocandin era" (16,56,57). Prior to the availability of the echinocandins, concern over the reduced azole susceptibility of C. glabrata was a major issue for clinicians (10,22,29,32,54).…”
Section: Resultsmentioning
confidence: 99%
“…achieve suitable growth for MIC testing by 24 h of incubation (14)(15)(16)36). Given the facts that a shorter incubation period is more efficient and practical for use in the clinical laboratory (16,36) and that research has shown that early/ correct antifungal treatment has a positive effect on outcomes for patients with candidemia (5,6,12,19,20,23,27,29,33,53), the CLSI has determined that fluconazole MICs may be used after a 24-h incubation, providing earlier clinically useful information to clinicians caring for patients with invasive candidiasis (IC) (31,36). Currently, the CLSI recommends that MICs for the newer triazoles, posaconazole and voriconazole, be read after 48 h of incubation for testing of Candida spp.…”
mentioning
confidence: 99%
“…There now are several lines of evidence that indicate that early and appropriate (correct dose and susceptible organism) antifungal therapy has a positive effect on outcomes and resource utilization for patients with candidemia (2,14,15,19,22,24,28,39). The choice of antifungal therapy may be optimized by the use of routine onsite antifungal susceptibility testing (4,5,8,13,16,18,23,27,37).…”
mentioning
confidence: 99%